2019
DOI: 10.2139/ssrn.3404309
|View full text |Cite
|
Sign up to set email alerts
|

The Industrial Revolution in Services

Abstract: for helpful discussions. The data from the US Census has been reviewed by the U.S. Census Bureau to ensure no confidential information is disclosed. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w25968.ack NBER working papers are circulated for discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(25 reference statements)
0
24
0
Order By: Relevance
“…Rinz (2018),Hsieh and Rossi-Hansberg (2019).Electronic copy available at: https://ssrn.com/abstract=3682745…”
mentioning
confidence: 99%
“…Rinz (2018),Hsieh and Rossi-Hansberg (2019).Electronic copy available at: https://ssrn.com/abstract=3682745…”
mentioning
confidence: 99%
“…Barcodes were a key component in a broad set of innovations that dramatically lowered the cost of managing inventory in retail supply chains. Scholars have suggested that this had far-reaching implications, including the rise of the big-box format (e.g., Holmes, 2001;Dunlop, 2001) and subsequent increases in industry concentration (e.g., Basker, Klimek, and Van, 2012;Hsieh and Rossi-Hansberg, 2019). This paper is the first to measure the effects of UPC adoption on upstream employment, revenue, product innovation, and industry-level imports, providing a natural complement to the literature on retail productivity (e.g., Foster, Haltiwanger, and Krizan, 2006;Basker, 2012) and a new addition to the empirical literature on the effects of industry standards.…”
Section: Discussionmentioning
confidence: 99%
“…Barcodes were a key component in a broad set of innovations that dramatically lowered the cost of managing inventory in retail supply chains. Scholars have suggested that this had far-reaching implications, including the rise of the big-box format (e.g., Holmes, 2001;Dunlop, 2001) and subsequent increases in industry concentration (e.g., Basker, Klimek, and Van, 2012;Hsieh and Rossi-Hansberg, 2019). This paper is the first to measure the effects of UPC adoption on upstream employment, revenue, product innovation, and industry-level imports, providing a natural complement to the literature on retail productivity (e.g., Foster, Haltiwanger, and Krizan, 2006;Basker, 2012) and a new addition to the empirical literature on the effects of industry standards.…”
Section: Discussionmentioning
confidence: 99%